Sustainable tourism in an ecologically critical area: Implications to Dahican and its threatened marine megafauna - Lea Jimenez; Bernadette Nanual; Diana Maria Margarita Verdote; Maria Jessica June abaja; Mario Khen Inabiogan; France Guillian Rapiz (Davao Research Journal)
The City of Mati, Davao Oriental is one of the few places that can boast of a wide variety of natural attractions ideal for promoting eco-tourism enterprises. Dahican Beach is unique because it is the habitat of several charismatic marine megafauna, namely: dugongs, whale sharks, dolphins, and three species of nesting marine turtles. Yet, very little is about the marine species that have made Dahican their home. In 2013, the Regional ICRM Center XI simultaneously conducted two studies in Dahican: one was the baseline study on the status of marine megafauna in Mayo Bay, and the other was a willingness-to-pay study for the feasibility of collecting environmental fees. Both projects have implications on the sustainability of these resources as well as that of future tourism endeavors. Around the same time, however, the operation of a personal watercraft (PWC) - popularly known as Jet Ski® had been observed in Dahican. Such an activity has and will result to a number of issues including but not limited to conflict with other beach recreationists, disruption in the conduct of RIC Xl's research, and the potentially grave threat to the survival of marine organisms, especially the large marine vertebrates. To elucidate to the reader the possible threats of PWCs on the marine wildlife of Dahican, a literature review is provided.